SINERGI CORPORATE SOCIAL RESPONSIBILITY (CSR) PT. BUKIT ASAM DAN HUBUNGAN MASYARAKAT (HUMAS) PADA LAYANAN KESEHATAN - Amalia, Risky; Ginting, Eraskaita; Ritonga, Muslimin (UNIVERSITAS STEKOM, 2025)
This study aims to explore the synergy between the Corporate Social Responsibility (CSR) program of PT. Bukit Asam and the Public Relations (PR) unit of Bukit Asam Medika Hospital (RSBAM) in delivering public health services. The free healthcare program implemented by the company is a tangible form of social responsibility aimed at improving the quality of health among communities living around the company’s operational area. Using a qualitative descriptive method, data were collected through interviews, field observations, and documentation studies. The findings reveal that the collaboration between CSR and PR is built on strong communication, structured coordination, and shared responsibilities, which contribute to effective program delivery. The community reported significant benefits, such as easier access to health services, increased awareness about health, and improved relations with the company. From a management perspective, this synergy also supports the company’s image and builds public trust. The PR unit plays a crucial role in managing communication and internal coordination, while the CSR team ensures continuity and sustainability of the program. Together, they form a solid partnership that enables the program to run efficiently and meet community needs. This research concludes that the collaborative model between CSR and PR can serve as a best practice example for other companies aiming to carry out meaningful social initiatives in the health sector. It is recommended that this model be maintained and further developed to ensure long-term social impact and corporate accountability.